2008
DOI: 10.1016/j.tins.2008.02.005
|View full text |Cite
|
Sign up to set email alerts
|

Circuit-based framework for understanding neurotransmitter and risk gene interactions in schizophrenia

Abstract: Many risk genes interact synergistically to produce schizophrenia and many neurotransmitter interactions have been implicated. We have developed a circuit-based framework for understanding gene and neurotransmitter interactions. NMDAR hypofunction has been implicated in schizophrenia because NMDAR antagonists reproduce symptoms of the disease. One action of antagonists is to reduce the excitation of fast-spiking interneurons, resulting in disinhibition of pyramidal cells. Overactive pyramidal cells, notably th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

43
847
1
10

Year Published

2009
2009
2012
2012

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 922 publications
(901 citation statements)
references
References 161 publications
(161 reference statements)
43
847
1
10
Order By: Relevance
“…This leads to a longer time constant of the calcium decay after a spike in the interneuron. It has been proposed that the reduction of PV in Schizophrenia is a compensatory mechanism which aims to increase the gain of the interneurons and therefore the inhibition (Lisman et al, 2008). However, we have shown in the GENE-SIS model that the longer inhibition by the Ca dynamics has no influence on the STDP curve.…”
Section: Discussionmentioning
confidence: 57%
See 2 more Smart Citations
“…This leads to a longer time constant of the calcium decay after a spike in the interneuron. It has been proposed that the reduction of PV in Schizophrenia is a compensatory mechanism which aims to increase the gain of the interneurons and therefore the inhibition (Lisman et al, 2008). However, we have shown in the GENE-SIS model that the longer inhibition by the Ca dynamics has no influence on the STDP curve.…”
Section: Discussionmentioning
confidence: 57%
“…This means that on the network level less NMDA activation will lead to more activity. This has been recently pointed out by Lisman et al (2008) who proposes that cells in fact reduce their PV concentration to "fake" the longer NMDA activation in interneurons. While this has no effect on the STDP curve this is an important property for network stability which leads to the last point, namely network effects.…”
Section: Discussionmentioning
confidence: 89%
See 1 more Smart Citation
“…This regimen also elicits alterations in N-acetylaspartate (NAA) and N-acetylaspartylglutamate (NAAG) in temporal cortex and hippocampus (Reynolds et al, 2005), and decreases 5HT2A receptor binding in the PFC (Steward et al, 2004) in close similarity to schizophrenia pathology (Laruelle et al, 1993;Nudmamud et al, 2003). Furthermore, while the behavioral and neurochemical effects of acute exposures to NMDA-R antagonists are believed to occur upon disinhibition of cortical excitatory activity due to increased sensitivity of inhibitory systems to blockade of NMDA-R function (Olney et al, 1999;Homayoun and Moghaddam, 2007;Lisman et al, 2008;Middleton et al, 2008), they do not lead to the enduring changes in PV-interneurons observed in schizophrenia. Repetitive exposures to NMDA-R antagonists, on the other hand, produce a reduction in GAD67 expression in PVinterneurons of rodents (Behrens et al, 2007 as well as decreased expression of parvalbumin in rodents and non-human primates (Cochran et al, 2002;Keilhoff et al, 2004;Rujescu et al, 2006;Morrow et al, 2007).…”
Section: Introductionmentioning
confidence: 99%
“…Alternativement, un composé qui se lierait au NTD des sous-unités GluN2 et en empêcherait la fermeture devrait aussi permettre une potentialisation des récepteurs NMDA [34]. De tels modulateurs positifs pourraient être utiles dans le cadre de thé-rapies contre des psychoses telles que la schizophrénie étant donné l'implication probable d'un déficit d'activité des récepteurs NMDA dans ces pathologies [39]. Au contraire, des inhibiteurs des récepteurs NMDA pourraient aider à lutter contre des pathologies impliquant une suractivité de ces récepteurs, par exemple lors d'ischémies cérébrales consécutives à un accident vasculaire cérébral [28], ou encore dans le cas de douleurs neuropathiques [7].…”
Section: Perspectives Pharmacologiquesunclassified